Heterogeneidade de habitats mantém alta substituição de traços funcionais do zooplâncton em um rio neotropical. - Ribeiro, Bárbhara Isabella Oenning (2019)
Functional beta diversity and its components (nestedness and turnover) are widely used to understand the ecosystem processes and conservation measures. From the classification of species, relating their functional characteristics (morphological, physiological and ecological), it is possible to obtain the functional variability of the community (functional beta diversity). This, in turn, is structured by habitat heterogeneity. Among the components of the aquatic community, zooplankton has a direct connection with ecosystem processes, contributing mainly to nutrient cycling and productivity. The objective of this study was test the relationship between total functional beta diversity and its components and habitats heterogeneity in a Neotropical river. The samples were obtained in ten points, in transect, along a section of the Paraná River. Samples were collected on August and November 2013 and February and May 2014, a total of 120 samples. The functional characterization of the zooplankton community and the heterogeneity was evaluated through PERMIDISP analysis. Generalized linear mixed models (GLMM) were generated test the relationship between functional beta diversity and its components (turnover and nesting) with heterogeneity. The turnover was explained by heterogeneity, and the model indicated that trait substitution was positively affected by increased habitat heterogeneity. Thus, increase in habitat heterogeneity led to an increase in the variation in the functional characteristics of the community. Nestedness was not explained by heterogeneity and presented a higher contribution to functional beta diversity when compared to turnover. Therefore, ours results suggest that habitat heterogeneity should be preserved in order to maintain zooplankton participation in ecosystem functioning.